Proportion of births protected against neonatal tetanus and its associated factors among mothers who gave birth within the past 6 months in Gozamn district, Northwest Ethiopia, 2022 - Anteneh Gashaw; Melaku Hunie; Eyuel Amare; Amare Zewdie; Mesfin Abebe; Muluken Demeke; Samuel Kefelegn; Daniel Yehualashet; Asrat Alemu; Yayeh Adamu; Tesfaye Gugsa; Anmut Tagele (Taylor & Francis Group, 2023)
Today, neonatal tetanus accounts for a significant portion of newborn and under−5 mortality - 40% and 57%, respectively - and is the most prevalent cause of neonatal mortality and morbidity, particularly in developing nations. As a result, more study on birth protection against neonatal tetanus is required because it is such a terrible condition with such a high death rate and there is a need for more recent evidence on it. From April 1 to 30, 2022, a community-based cross-sectional survey was carried out in the Gozamn district of Northwest Ethiopia. A two-stage stratified sampling procedure was applied, with an overall sample size of 831. The data were gathered using a pre-tested, structured questionnaire. It was then checked, cleaned, and entered into Epidata software version 4.6 before being exported to Stata version 14 for analysis. The proportions of birth protected against neonatal tetanus were 58.57% (95% CI (55.15-61.89%) in the study. Mother who had radio (AOR = 3.09,95%CI: 2.09, 4.56), mother who travel less than one hour to reach nearest health facility (AOR = 1.96,95%CI: 1.23,3.10), mother who gave birth of their last child in the health institution (AOR = 4.17,95%CI:2.39,7.28), mothers who had information from health professional (AOR = 2.56,95%CI:1.56,4.19) and > 4 ANC visit (AOR = 2.57,95%CI:1.55,4.26) were positive predictors of birth protected against neonatal tetanus. Low levels of maternal protection against neonatal tetanus were seen in this study location. To enhance the percentage of births protected against neonatal tetanus, professional-based guidance regarding the TT vaccine are essential.